Under Hoffman's Framework: The Analysis of Code-Switching and Code-Mixing in Leonardo Edwin’s Youtube Video Channel - Adinda Meisya; Eva Nurchurifiani; Dian windriani (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This research focused on analyzing the types and reasons for code-switching and code-mixing that occur in five videos on Leonardo Edwin’s YouTube channel. The aims of this research were: (1) to identify the types of code-switching used by Leonardo Edwin on his YouTube channel, (2) to identify the types of code-mixing used by Leonardo Edwin on his YouTube channel, and (3) to determine the reasons for the code-switching and code-mixing employed by Leonardo Edwin on his YouTube channel. The objects of this research were five videos from Leonardo Edwin's YouTube channel, titled Alaska. To conduct this research, the researcher employed a descriptive qualitative method. In analyzing the data, the researcher used content analysis based on the Hoffman framework. The results of this research show that the dominant type of code-switching is inter-sentential code-switching, accounting for 58.07%, while the dominant type of code-mixing is intra-sentential code-mixing, accounting for 68%. The primary reason for code-switching and code-mixing is discussing specific topics, which constitutes 80.77%. The implications of this study are to provide insights into the types and reasons for code-switching and code-mixing used by Leonardo Edwin and to illustrate how bilingual individuals utilize code-switching and code-mixing on YouTube.